2016
DOI: 10.1590/1414-431x20165258
|View full text |Cite
|
Sign up to set email alerts
|

Brain caspase-3 and intestinal FABP responses in preterm and term rats submitted to birth asphyxia

Abstract: Neonatal asphyxia can cause irreversible injury of multiple organs resulting in hypoxic-ischemic encephalopathy and necrotizing enterocolitis (NEC). This injury is dependent on time, severity, and gestational age, once the preterm babies need ventilator support. Our aim was to assess the different brain and intestinal effects of ischemia and reperfusion in neonate rats after birth anoxia and mechanical ventilation. Preterm and term neonates were divided into 8 subgroups (n=12/group): 1) preterm control (PTC), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
2

Year Published

2019
2019
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
(43 reference statements)
0
2
0
2
Order By: Relevance
“…In a study, investigating IFABP and brain-caspase-3 responses in preterm and term mice in which an experimental asphyxiated model was established, it was reported that the expression of these markers in the term mice was higher than the preterm ones. It was indicated that the expression of the markers by the gestational age may be related to the different levels of the expression (Figueira et al 2016). It has been reported that a significant portion of TFF3 in rats is expressed late in term pregnancy (Lin et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…In a study, investigating IFABP and brain-caspase-3 responses in preterm and term mice in which an experimental asphyxiated model was established, it was reported that the expression of these markers in the term mice was higher than the preterm ones. It was indicated that the expression of the markers by the gestational age may be related to the different levels of the expression (Figueira et al 2016). It has been reported that a significant portion of TFF3 in rats is expressed late in term pregnancy (Lin et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Cascade can activate Ca 2þ -dependent enzymes including calpain and caspase-3. 27 a-II spectrin can be degraded by alpain and caspase-3, and the cleavage products are named SBDP145, SBDP150 and SBDP120 respectively according to their quality characteristics after electrophoresis. Previous studies showed that SBDP145, SBDP150, and SBDP120 increased in varying degrees in the cerebrospinal fluid of patients with severe brain trauma and in the serum of animals with brain injury or cerebral hypoxia-ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…Além disso, as membranas neuronais são ricas em ácidos graxos poli-insaturados, tornando-se alvo para a peroxidação lipídica causada pelo EO (49). Ratos submetidos a hipóxia tiveram aumento do EO, aferido através do aumento da MDA no cérebro e no intestino e da C3 a nível cerebral (116). No traumatismo cerebral, a OHB reduz os níveis do TNF-α e de mieloperoxidases, o que significa redução no ac mulo local de neutrófilos, resultando em menor liberação de radicais livres (117).…”
Section: Discussionunclassified